Terahertz time-domain attenuated total reflection spectroscopy integrated with a microfluidic chip - Fu, Ying; Chen, Tunan; Chen, Ligang; Guo, Yuansen; Yang, Zhongbo; Mu, Ning; Feng, Hua; Zhang, Mingkun; Wang, Huabin (Frontiers in Bioengineering and Biotechnology, 2023)
The integration of a microfluidic chip into terahertz time-domain attenuated total reflection (THz TD-ATR) spectroscopy is highly demanded for the accurate measurement of aqueous samples. Hitherto, however little work has been reported on this regard. Here, we demonstrate a strategy of fabricating a polydimethylsiloxane microfluidic chip (M-chip) suitable for the measurement of aqueous samples, and investigate the effects of its configuration, particularly the cavity depth of the M-chip on THz spectra. By measuring pure water, we find that the Fresnel formulae of two-interface model should be applied to analyze the THz spectral data when the depth is smaller than 210 μm, but the Fresnel formula of one-interface model can be applied when the depth is no less than 210 μm. We further validate this by measuring physiological solution and protein solution. This work can help promote the application of THz TD-ATR spectroscopy in the study of aqueous biological samples.